(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Human imagination and literature are the closest mates, who in their turn can do miracles. Literature is the space where imagination has no check. That is a reason, many modern scientific inventions see their initial accomplishment in literature. In the modern times we have humanoid robots, which were conceived in the form of Monsters in literature way before science made a breakthrough. In twentieth century, science, literature, media, and human society at large has been taken over by simulations